PENGARUH KOMUNIKASI DOKTER TERHADAP KESEMBUHAN PASIEN RAWAT JALAN - Saleh, Gunawan; Hendra, Muhammad David (Master of Communication Science Program, Universitas Diponegoro, 2019)
A well constructed communications between doctorand patient is one of the keys to successful doctorsin providing medical service efforts. Unsuccessfuldoctor medical problems if communicated well willnot give rise to a dispute, but rather a medicalsuccess achieved whatsoever if it is notcommunicated, and patients feel not satisfied canalso give rise to disputes or medical disputes. In the profession of medicine communicationbetween doctors and patients is the mostimportant component and is important in giving thewaiter points towards the patient. The effectivenessof communication between doctor and patient willcreate success in the process of patient care,treatment given aims to improve the health statusof the patient. Health communication include the utilization ofservices of communication to convey messages andinfluence the decision making process related tohealth management and enhancement efforts byindividuals and community. In addition, it alsoincludes health communication activitiesdisseminate information about health to thecommunity in order to be achieved conduct healthyliving, creating awareness, change attitudes andmotivate individuals to adopt the recommendedhealthy behaviors become the main purpose of health communication.